Low-creep cap ply material prepared from recycled polyester and preparation method of low-creep cap ply material
Through the preparation of regenerated polyester materials, melt spinning, yarn twisting and glue dipping processes, the problem of poor dimensional stability of the existing tire crown belt material under high temperature conditions is solved, and the polyester crown belt material with low creep and high strength characteristics is achieved, reducing costs and improving tire uniformity.
Patent Information
- Application Number
- CN202311744539.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-19
- Publication Date
- 2025-03-11
AI Technical Summary
The existing tire crown belt materials such as nylon 66 cords have defects such as low modulus, large high temperature shrinkage, poor dimensional stability and large moisture rebate during use, resulting in poor tire uniformity.
Recycled polyester is used to prepare a low-creep crown belt material. Through melt spinning, twisting and impregnation processes, the p-Tol content is controlled to be less than 120ppm, thereby improving the strength and dimensional stability of the polyester.
The polyester crown belt material with low creep, high strength and high dimensional stability is achieved, reducing costs and maintaining dimensional stability under high temperature conditions, avoiding the tire "flat spot" phenomenon.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high molecular polyester materials, and in particular to a low creep cap layer material prepared by using recycled polyester and a preparation method thereof. Background Art
[0002] As the only part connecting the car and the road, the tire bears various forces from the road and the whole vehicle; the mechanical properties of the tire have an important impact on the overall vehicle's handling stability, comfort, passability and safety. The main structure of the tire includes the tread, sidewall, cord layer, airtight layer, belt layer and cap layer. The cap layer is located above the belt layer and is usually wound in strips along the circumferential direction. It is responsible for preventing the steel cord layer below from displacement or detachment during tire driving, thereby ensuring the dimensional integrity and stability of the tire at high speeds.
[0003] At present, the cap layer on the market is mainly made of polyhexamethylene adipamide (nylon 66) material, because it contains a large number of flexible -CH2- groups and is connected by polar amide bonds to form linear long-chain molecules. The molecular chain is relatively flexible and has good flexibility. At the same time, the polar amide groups are conducive to forming a large number of hydrogen bonds with the rubber matrix, thereby improving the adhesion between the nylon 66 cord and the rubber matrix. Like rayon cord, nylon 66 cord has a large number of polar groups on the surface, so only traditional RFL dipping liquid treatment is required to meet the interface adhesion requirements. However, based on the characteristics of the nylon 66 high molecular polymer structure, nylon 66 cord has the defects of low modulus, large high temperature shrinkage, poor dimensional stability and high moisture regain. The tire is prone to "flat spots" during use, resulting in poor tire uniformity.
[0004] High modulus low shrinkage (HMLS) polyester cord (PET) has the characteristics of high modulus and low high temperature shrinkage compared to nylon cord, which can effectively solve the problem of tire sidewall depression and "flat spot" of nylon cord tire. Due to the low dry heat shrinkage rate of HMLS polyester cord, the outer edge size of the tire can meet the index requirements after high temperature vulcanization, and no post-vulcanization inflation process is required, which is conducive to saving energy and improving efficiency.
[0005] p-Toluic acid (p-Tol) is produced by the cracking of polyester at high temperature, and its content has an important influence on the quality of polyester. Recycled polyester (rPET) is produced by the cracking of PET at high temperature, and the product is washed with hot water. After washing, the content of p-Tol will be significantly reduced, which is conducive to reducing the production of hair in the spinning process. The polyester cap layer material obtained has the advantages of low creep (Creep), high strength and high dimensional stability (DSI). Therefore, the present application designs a low creep cap layer material and preparation method prepared by recycled polyester through the above characteristics, and prepares a polyester cap layer material with low creep, high strength and high dimensional stability through the difference in impurity content between virgin polyester and chemically recycled polyester, which obviously has practical significance. Summary of the invention
[0006] The purpose of the present invention is to provide a low creep cap layer material prepared by using recycled polyester and a preparation method thereof.
[0007] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing a low creep cap layer material using recycled polyester, comprising the following steps:
[0008] S1, melt spinning process: melt extruding, spinning, cooling, pulling, shaping, and winding the recycled polyester raw material; the recycled polyester raw material is a polyester raw material with a p-Tol content of less than 120ppm;
[0009] S2, twisting process: twisting the wound yarn, with the twist being designed to be no more than 46X46T / 100mm;
[0010] S3, dipping process.
[0011] Preferably, in step S1, the stretching ratio of the spinneret during the spinning process is 800-2100.
[0012] Preferably, in step S1, the spinneret stretching ratio during the spinning process is 1000-1900.
[0013] Preferably, the melt extrusion method in step S1 includes inputting the raw material into a screw extruder for high-temperature melting and extruding it into a spinning assembly, the temperature of each zone of the screw is 280-320°C, the head pressure is 10-17MPa, and the temperature of the cooling zone is 23-65°C.
[0014] Preferably, the temperature of each zone of the screw is 290-305°C, and the head pressure is 12-16 MPa.
[0015] Preferably, in step S2, the twist designed during the yarn twisting process is less than 38X38 T / 100mm.
[0016] Preferably, in step S3, the specific method of the dipping process includes: subjecting the twisted yarn prepared in step S2 to high temperature heat treatment, and using a D417 dipping method or a one-bath dipping method to enable the yarn to obtain good adhesion with the rubber.
[0017] Preferably, the temperature of the twisted yarn in the drying zone is 140-160° C., the drying time is 150s-240s, and the temperature in the setting zone is 200-240° C., the setting time is 150-200s.
[0018] In the above, the method for detecting the p-Tol content in the polyester raw material comprises the following steps:
[0019] S11, cracking the raw material to be tested, decomposing the raw material to be tested into small molecules and producing trace impurities, extracting the small molecules and trace impurities, filtering, washing, and drying to obtain the object to be tested;
[0020] S12, preparing a sample from the test object prepared in step S11, analyzing the sample using a high-efficiency capillary chromatographic column, and testing the impurity content after polyester cracking.
[0021] Preferably, the small molecule comprises PTA (terephthalic acid).
[0022] Preferably, the cleavage in step S11 is carried out by alkaline alcoholysis or alkaline hydrolysis, the cleavage temperature is 120-220° C., and the reaction time is 2-7 hours.
[0023] Preferably, the cracking in step S11 adopts alkaline alcoholysis method, the alcohol used in the alkaline alcoholysis method is methanol or ethylene glycol, and the mass ratio of the raw material to be tested to the alcohol is 1:3-7.
[0024] Preferably, the cleavage in step S11 is performed by alkaline hydrolysis, and the water used in the alkaline hydrolysis is deionized water; the mass ratio of the raw material to be tested to water is 1:3-7.
[0025] Preferably, in step S11, the cracking reaction process further includes adding a catalyst, the catalyst includes sodium carbonate, and the mass ratio of the catalyst to the raw material to be tested is 0.5 to 1:1.
[0026] Preferably, the specific method of the alkaline alcoholysis method includes: adding the raw material to be tested, alcohol and catalyst into a three-necked flask in proportion, placing the three-necked flask in an oil bath heating device, installing a condensing reflux device, starting stirring, and the stirring rate is 500-1500rpm; cooling to 150°C after the reaction is completed and stopping stirring, replacing the mechanical stirring reflux device with a distillation device, reducing the pressure with a water pump, heating to evaporate the alcohol, and stopping heating after distilling until no distilled components are produced; during the reaction, when the system is heated to 130°C, bubbles can be seen to be generated, and the flask gradually becomes a white thick slurry.
[0027] Preferably, the mass ratio of the raw material to be tested, the alcohol and the catalyst is 1:5-8:0.5-0.8.
[0028] Preferably, in step S11, the preparation method of the analyte includes: after the cleavage reaction is completed, hot water is added to the reaction container, stirring to completely dissolve the solid in the reaction container, filtering to remove insoluble matter, transferring the filtered solution to a beaker, and performing acid-base titration with dilute sulfuric acid to pH = 1.5 to 2.0 while stirring, and terminating the titration reaction; after multiple filtration and washing, placing it in an oven to dry, the analyte can be obtained.
[0029] Preferably, the temperature of the hot water is 85-95°C, preferably 90°C.
[0030] Preferably, the concentration of the dilute sulfuric acid is 0.4-0.6 mol / L.
[0031] Preferably, in step S12, the specific method of preparing the test object prepared in step S1 into a sample includes: adding ammonia water to the test object prepared in step S11, ultrasonically dissolving it, filtering it after dissolution to remove insoluble matter, and placing the filtrate in a sample bottle to prepare the sample.
[0032] Preferably, in step S12, when a high-efficiency capillary chromatographic column is used to analyze the sample, the corresponding peak position of the chromatogram is that of the organic impurity p-Tol peak at 6.5-7.0 min.
[0033] Preferably, the inner diameter of the capillary is 60 μm to 80 μm, and the effective length is 50 cm to 70 cm.
[0034] The present application also claims protection for a low creep cap layer material made from recycled polyester, which is prepared using the method for preparing a low creep cap layer material made from recycled polyester as described above.
[0035] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:
[0036] Compared with nylon cap layer materials, the low creep cap layer material prepared by using recycled polyester in the present invention has excellent creep characteristics and good dimensional stability, and can save 4% in cost, and is an ideal material to replace nylon cap layer. DETAILED DESCRIPTION
[0037] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] The method for detecting the p-Tol content in the polyester raw material in this embodiment comprises the following steps:
[0039] S11, cracking the raw material to be tested, decomposing the raw material to be tested into small molecules and producing trace impurities, extracting the small molecules and trace impurities, filtering, washing, and drying to obtain the object to be tested;
[0040] S12, preparing a sample from the test object prepared in step S11, analyzing the sample using a high-efficiency capillary chromatographic column, and testing the impurity content after polyester cracking.
[0041] Furthermore, the small molecule includes PTA (terephthalic acid).
[0042] Furthermore, the cleavage in step S11 is carried out by alkaline alcoholysis or alkaline hydrolysis, the cleavage temperature is 120 to 220° C., and the reaction time is 2 to 7 hours.
[0043] Furthermore, the cracking in step S11 adopts alkaline alcoholysis method, the alcohol used in the alkaline alcoholysis method is methanol or ethylene glycol, and the mass ratio of the raw material to be tested to the alcohol is 1:3-7.
[0044] Furthermore, the cleavage in step S11 is performed by alkaline hydrolysis, and the water used in the alkaline hydrolysis is deionized water; the mass ratio of the raw material to be tested to water is 1:3-7.
[0045] Furthermore, in step S11, the cracking reaction process also includes adding a catalyst, the catalyst includes sodium carbonate, and the mass ratio of the catalyst to the raw material to be tested is 0.5 to 1:1.
[0046] Furthermore, the specific method of the alkaline alcoholysis method includes: adding the raw material to be tested, alcohol and catalyst into a three-necked flask in proportion, placing the three-necked flask in an oil bath heating device, installing a condensing reflux device at the same time, starting stirring, and the stirring rate is 500-1500rpm; cooling to 150°C after the reaction is completed and stopping stirring, replacing the mechanical stirring reflux device with a distillation device, reducing the pressure with a water pump, heating to evaporate the alcohol, and stopping heating after distilling until there is no distilled component; during the reaction, when the system is heated to 130°C, bubbles can be seen to be generated, and the flask gradually becomes a white thick slurry.
[0047] Furthermore, the mass ratio of the raw material to be tested, the alcohol and the catalyst is 1:5-8:0.5-0.8.
[0048] Furthermore, in step S11, the preparation method of the analyte includes: after the cleavage reaction is completed, hot water is added to the reaction container, stirring to completely dissolve the solid in the reaction container, filtering to remove insoluble matter, transferring the filtered solution to a beaker, and performing acid-base titration with dilute sulfuric acid to pH = 1.5 to 2.0 while stirring, and terminating the titration reaction; after multiple filtration and washing, placing it in an oven to dry, the analyte can be obtained.
[0049] Furthermore, the temperature of the hot water is 85-95°C, preferably 90°C.
[0050] Furthermore, the concentration of the dilute sulfuric acid is 0.4-0.6 mol / L.
[0051] Furthermore, in step S12, the specific method of preparing the test object prepared in step S1 into a sample includes: adding ammonia water to the test object prepared in step S11, ultrasonically dissolving it, filtering it after dissolution to remove insoluble matter, and placing the filtrate in a sample bottle to prepare the sample.
[0052] Furthermore, in step S12, when a high-efficiency capillary column is used to analyze the sample, the corresponding peak position of the chromatogram is that the peak position of the organic impurity p-Tol peak on the chromatogram is between 6.5 and 7.0 min.
[0053] Furthermore, the inner diameter of the capillary is 60 μm to 80 μm, and the effective length is 50 cm to 70 cm.
[0054] The difference between virgin polyester and chemically recycled polyester is that chemically recycled polyester undergoes a high-temperature cracking and refining process, and will produce small molecules and impurities after depolymerization. The impurities include p-toluic acid (p-Tol), p-carboxybenzaldehyde (4CBA), and benzoic acid (BA); p-Tol acts as an inhibitor in the reaction, which will cause the molecular chain to lose its activity and the chain end to be closed, thereby stopping the growth of molecular weight. Its presence directly affects the crystallization properties, molecular weight and distribution of polyester, thereby having an important impact on the intrinsic quality, spinnability and quality of polyester; by selecting at least 20 chemically recycled polyesters, the results show that the chemically recycled polyester has a good performance in the production of polyester and a good performance in the production of polyester. Polyester and at least 20 virgin polyesters were used as samples, and the samples were subjected to high-temperature pyrolysis, sample extraction, and high-efficiency capillary column analysis to obtain their p-Tol content, 4CBA content, and BA content. The p-Tol content, 4CBA content, and BA content were used as sample data, and the sample labels were input into the linear model for training. The training results showed that when the p-Tol content was less than 120ppm, the raw material to be tested was chemically recycled polyester, and when the p-Tol content was greater than 120ppm, the raw material to be tested was virgin polyester; and 4CBA and BA did not have comparison rules. This is because p-Tol is easily soluble in hot water, and some of the impurities will be washed away under hot water; the p-Tol content of the chemically recycled polyester material after repolymerization will be reduced compared with the virgin polyester.
[0055] Example 1
[0056] This embodiment discloses a method for preparing a low creep cap layer material using recycled polyester, comprising the following steps:
[0057] S1, melt spinning process: melt extrusion, spinning, cooling, drawing, shaping, and winding of a polyester raw material with a p-Tol content of 80 ppm to form a filament; during the spinning process, the spinneret stretching ratio is 1265, the screw 1-6 zone temperatures are 280 / 280 / 290 / 305 / 305 / 305 respectively, the die pressure is 15 MPa, and the cooling zone temperature is 28°C;
[0058] S2, twisting process: twisting the wound yarn obtained in step S1, and the twist degree designed in the twisting process is 26X26 T / 100mm;
[0059] S3, dipping process: the twisted yarn prepared in step S2 is subjected to high temperature heat treatment, and combined with D417 dipping method to make the yarn have good adhesion with rubber; wherein the temperature of the yarn in the drying zone is 160°C, the drying time is 200s, the temperature of the setting zone is 240°C, and the setting time is 180s.
[0060] Furthermore, the D417 dipping method uses a meta-methyl system dipping solution.
[0061] Example 2
[0062] The embodiment of the present invention discloses a method for preparing a low creep cap layer material using recycled polyester, comprising the following steps:
[0063] S1, melt spinning process: melt extrusion, spinning, cooling, pulling, shaping, and winding of a polyester raw material with a p-Tol content of 80 ppm to form a filament, wherein the spinneret stretching ratio during the spinning process is 1265, the screw 1-6 zone temperatures are 280 / 280 / 290 / 305 / 305 / 305 respectively, the die pressure is 15 MPa, and the cooling zone temperature is 28°C;
[0064] S2, twisting process: twisting the wound yarn obtained in step S1, and the twist degree designed in the twisting process is 32X32 T / 100mm;
[0065] S3, dipping process: The twisted yarn prepared in step S2 is subjected to high temperature heat treatment, and the D417 dipping method is used to make the yarn have good adhesion with rubber. The temperature of the yarn in the drying zone is 160°C, the drying time is 200s, the temperature of the setting zone is 240°C, and the setting time is 180s.
[0066] Furthermore, the D417 dipping method uses a meta-methyl system dipping solution.
[0067] Example 3
[0068] The embodiment of the present invention discloses a method for preparing a low creep cap layer material using recycled polyester, comprising the following steps:
[0069] S1, melt spinning process: melt extrusion, spinning, cooling, pulling, shaping, and winding of a polyester raw material with a p-Tol content of 80 ppm to form a filament, wherein the spinneret stretching ratio during the spinning process is 1265, the screw 1-6 zone temperatures are 280 / 280 / 290 / 305 / 305 / 305 respectively, the die pressure is 15 MPa, and the cooling zone temperature is 28°C;
[0070] S2, twisting process: twisting the wound yarn obtained in step S1, and the twist degree designed in the twisting process is 38X38 T / 100mm;
[0071] S3, dipping process: The twisted yarn prepared in step S2 is subjected to high temperature heat treatment, and the D417 dipping method is used to make the yarn have good adhesion with rubber. The temperature of the yarn in the drying zone is 160°C, the drying time is 200s, the temperature of the setting zone is 240°C, and the setting time is 180s.
[0072] Furthermore, the D417 dipping method uses a meta-methyl system dipping solution.
[0073] Example 4
[0074] The embodiment of the present invention discloses a method for preparing a low creep cap layer material using recycled polyester, comprising the following steps:
[0075] S1, melt spinning process: melt extrusion, spinning, cooling, pulling, shaping, and winding of polyester raw materials with a p-Tol content of 80ppm to form yarn. During the spinning process, the spinneret stretching ratio is 1265, the temperatures of screw zones 1-6 are 280 / 280 / 290 / 305 / 305 / 305 respectively, the die pressure is 15MPa, and the temperature of the cooling zone is 28°C;
[0076] S2, yarn twisting process: twisting the wound yarn obtained in step S1, and the twist degree designed in the yarn twisting process is 26X26T / 100mm;
[0077] S3, dipping process: The twisted yarn prepared in step S2 is subjected to high temperature heat treatment and combined with a one-bath dipping method to make the yarn have good adhesion with rubber. The temperature of the yarn in the drying zone is 150°C, the drying time is 220s, the temperature of the setting zone is 245°C, and the setting time is 200s.
[0078] Comparative Example 1
[0079] The embodiment of the present invention discloses a method for preparing a low creep cap layer material using recycled polyester, the process comprising the following steps:
[0080] S1. Melt spinning process: melt-extrude, spin, cool, pull, shape and wind the polyester raw material with a p-Tol content of 150 ppm; during the spinning process, the spinneret stretching ratio is 1265, the screw 1-6 zone temperatures are 285 / 285 / 300 / 305 / 305 / 300 respectively, the die pressure is 12 MPa, and the cooling zone temperature is 30°C.
[0081] S2, twisting process: twisting the wound yarn obtained in step S1, and the twist designed in the twisting process is 26X26T / 100mm.
[0082] S3, dipping process: The twisted yarn prepared in step S2 is subjected to high temperature heat treatment, and the D417 dipping method is used to make the yarn have good adhesion with rubber. The temperature of the yarn in the drying zone is 160°C, the drying time is 200s, the temperature of the setting zone is 240°C, and the setting time is 180s.
[0083] Furthermore, the D417 dipping method uses a meta-methyl system dipping solution.
[0084] Comparative Example 2
[0085] The embodiment of the present invention discloses a method for preparing a low creep cap layer material using recycled polyester, comprising the following steps:
[0086] S1, melt spinning process: melt extrusion, spinning, cooling, pulling, shaping, and winding of a polyester raw material with a p-Tol content of 150ppm to form a filament; during the spinning process, the spinneret stretch ratio is 1265, the temperatures of screw zones 1-6 are 280 / 280 / 290 / 305 / 305 / 305 respectively, the die pressure is 15MPa, and the temperature of the cooling zone is 28°C;
[0087] S2, twisting process: twisting the wound yarn obtained in step S1, and the twist degree designed in the twisting process is 26X26 T / 100mm;
[0088] S3, dipping process: The twisted yarn prepared in step S2 is subjected to high temperature heat treatment and combined with a one-bath dipping method to make the yarn have good adhesion with rubber. The temperature of the yarn in the drying zone is 150°C, the drying time is 220s, the temperature of the setting zone is 245°C, and the setting time is 200s.
[0089] Comparative Example 3
[0090] The embodiment of the present invention discloses a method for preparing a low creep cap layer material using recycled polyester, the process comprising the following steps:
[0091] S1. Melt spinning process: melt extrude, spin, cool, draw, shape and wind nylon 66 raw materials to make yarn.
[0092] S2, yarn twisting process: twisting the wound yarn obtained in step S1, and the twist degree designed in the yarn twisting process is 26X26T / 100mm;
[0093] S3, dipping process: The twisted yarn prepared in step S2 is subjected to high temperature heat treatment and combined with a one-bath dipping method to make the yarn have good adhesion with rubber. The temperature of the yarn in the drying zone is 150°C, the drying time is 220s, the temperature of the setting zone is 245°C, and the setting time is 200s.
[0094] In the preparation methods described in the above Examples 1-4 and Comparative Examples 1-3, the polyester raw material used in Examples 1-4 is recycled polyester, while the polyester raw material used in Comparative Examples 1-3 is virgin polyester. The low creep cap layer material prepared using recycled polyester by the preparation methods described in the above Examples 1-4 and Comparative Examples 1-3 was subjected to physical property characterization, and the results of the physical property characterization are shown in Table 1 below.
[0095] Table 1
[0096]
[0097] As can be seen from Table 1, the p-Tol content in the PET raw material is reduced, and the creep and strength after dipping are better. The creep and dimensional stability of the low p-Tol polyester shown in Examples 1-3 after dipping are significantly better than the N66 cap layer product shown in Comparative Example 3, and it is an ideal material to replace the N66 cap layer product. The above description of the disclosed embodiments enables professionals and technicians in this field to implement or use the present invention. Various modifications to these embodiments will be obvious to professionals and technicians in this field, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a low creep cap layer material using recycled polyester, characterized in that: The following steps are involved: S1, melt spinning process: melt extruding, spinning, cooling, pulling, shaping, and winding the recycled polyester raw material; the recycled polyester raw material is a polyester raw material with a p-Tol content of less than 120ppm; S2, twisting process: twisting the wound yarn, with the twist being designed to be no more than 46X46T / 100mm; S3, dipping process.
2. The method for preparing a low creep cap layer material using recycled polyester according to claim 1, characterized in that: In step S1, the stretching ratio of the spinneret during the spinning process is 800-2100.
3. The method for preparing a low creep cap layer material using recycled polyester according to claim 2, characterized in that: In step S1, the spinneret stretching ratio during the spinning process is 1000-1900.
4. The method for preparing a low creep cap layer material using recycled polyester according to claim 1, characterized in that: The melt extrusion method in step S1 includes inputting the raw material into a screw extruder for high-temperature melting and extruding it into a spinning assembly, the temperature of each zone of the screw is 280-320°C, the head pressure is 10-17MPa, and the temperature of the cooling zone is 23-65°C.
5. The method for preparing a low creep cap layer material using recycled polyester according to claim 4, characterized in that: The temperature of each zone of the screw is 290-305℃, and the head pressure is 12-16MPa.
6. The method for preparing a low creep cap layer material using recycled polyester according to claim 1, characterized in that: In step S2, the twist designed during the yarn twisting process is less than 38X38T / 100mm.
7. The method for preparing a low creep cap layer material using recycled polyester according to claim 1, characterized in that: In step S3, the specific method of the dipping process includes: subjecting the twisted yarn prepared in step S2 to high temperature heat treatment, and using a D417 dipping method or a one-bath dipping method to enable the yarn to obtain good adhesion with the rubber.
8. The method for preparing a low creep cap layer material using recycled polyester according to claim 7, characterized in that: The temperature of the twisted yarn in the drying zone is 140-160°C, the drying time is 150s-240s, the temperature in the setting zone is 200-240°C, and the setting time is 150-200s.
9. A low creep cap layer material prepared by using recycled polyester, characterized in that: The low creep cap layer material is prepared by the method for preparing the low creep cap layer material using recycled polyester as described in any one of claims 1 to 8.
Citation Information
Patent Citations
Method for identifying regenerated polyester generated through chemical recycling method
CN105388241A
Cap ply reinforcement strip in pneumatic tire
CN105579249A
Polyester tire cord and radial tire using same
CN111278665A
Polyester recycling process
CN115989122A
High tenacity polyethylene naphthalate tire cord, andhigh performance tire producted by the same
KR1020050012442A
Cited By
Low-heat seam allowance rubber sheet glue as well as preparation method and application thereof
CN120682543A